2017
DOI: 10.1007/s12098-017-2323-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Tissue Transglutaminase with Modified Marsh Grading in Celiac Disease: A Prospective Cohort Study

Abstract: Serum tTGA levels can be used to predict villous atrophy and biopsy may be avoided in strongly suspected cases with more than 9 times of cut-offs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Anti - tTG rendered a 90% positive predictive value, which was correlated with the antibody titer with higher titers correlating with higher predictive values (15, 18). In addition, Elitsur et al, noted that anti - tTG antibody titer is three times higher than upper limits is not a good representative of CD in children (19).…”
Section: Resultsmentioning
confidence: 93%
“…Anti - tTG rendered a 90% positive predictive value, which was correlated with the antibody titer with higher titers correlating with higher predictive values (15, 18). In addition, Elitsur et al, noted that anti - tTG antibody titer is three times higher than upper limits is not a good representative of CD in children (19).…”
Section: Resultsmentioning
confidence: 93%
“…Jora et al also performed similar type of study on marsh grading of duodenal histopathology in Celiac disease (CD) Waheed N et al from Lahore, Pakistan concluded in his study that celiac disease is not a rare disease in Asia, but an under diagnosed entity. 12,13 He conducted a descriptive cross-sectional study among 126 patients presenting in emergency room (ER) with profuse diarrhoea leading to severe dehydration, neuromuscular weakness, metabolic acidosis and electrolyte abnormalities. All patients met the standard diagnostic criteria for celiac disease including: modified Marsh…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in a study conducted by Jora R et al and found similar study to the present study. They conducted study among 52 children of age 2-18 years and found that most common clinical symptom among children was diarrhea followed by abdominal distention, pain in abdomen, anorexia, constipation, , edema, vitamin deficiencies, clubbing and mouth ulcers (12).…”
Section: Discussionmentioning
confidence: 99%